Hanging, crushing, and shooting: animals, violence and child-rearing in Bronte fiction - Shuttleworth, S (Cambridge University Press, 2019)
Ranging across novels by Anne, Emily and Charlotte Brontë, Sally Shuttleworth’s chapter investigates the animal/human (and animal/child) divide as envisaged through violence, complicity and humane necessity. The idea of the human was interwoven with that of the animal for the Brontës more so than for any other novelists in the nineteenth century, and Shuttleworth addresses in detail three key moments of animal cruelty: the hanging of Isabella’s dog in Wuthering Heights, the crushing of birds in Agnes Grey, and the shooting of Victor’s dog in The Professor. Shuttleworth sets her close reading of these scenes of torture in the context of contemporary medical and educational literature on child development. In practices of child-rearing, particularly the training of boys, kindness to animals was taken up in domestic conduct manuals as a form of moral education. The chapter also explores the interface between the child and the animal in light of the vivisection debates; rabies and passion in the Victorian cultural imaginary; and the visual imagination (William Hogarth’s prints depicting The Four Stages of Cruelty).